Cultural and Civilizational Origins of Armenia’s “soft power” Policy - Yengoyan, Paylak (YSU Journal of International Affairs, 2022)
The Armenian and Chinese civilizations are among the oldest in the world. Despite the difference in geographical location, scale and population, these two nations have common ideas about international life, and, in particular, the use of soft power both in foreign policy and directed “inward” to preserve identity and cohesion on the grounds of the national culture. At present, the vast majority of the Armenian people are in a completely different social and cultural environment. The issue arises about preserving the Armenian identity among the Diaspora, its culture, language, religion and the cohesion of the entire Armenian nation. In this regard, it is necessary to use the successful experience of China, which has relatively recently used soft power in its foreign policy. One of the main tools of such a policy of the PRC is the propaganda of its unique civilizational value system, which is carried out with different methods and with the help of the foreign diaspora as well.